2005
DOI: 10.1111/j.1742-4658.2005.04599.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor agonists inhibit tissue factor expression in macrophages

Abstract: Exposure of blood to tissue factor (TF) rapidly initiates the coagulation serine protease cascades. TF is expressed by macrophages and other types of cell within atherosclerotic lesions and plays an important role in thrombus formation after plaque rupture. Macrophage TF expression is induced by pro‐inflammatory stimuli including lipopolysaccharide (LPS), interleukin‐1β and tumor necrosis factor‐α. Here we demonstrate that activation of liver X receptors (LXRs) LXRα and LXRβ suppresses TF expression. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 52 publications
2
51
1
Order By: Relevance
“…Our results with LPS-treated cells support these observations, but the fact that the inflammatory response to IFN-g remains almost unchanged after cholesterol loading is intriguing and may help explain why a considerable percentage of foam cells within established atherosclerotic lesions still display a classically activated phenotype (49). Remarkably, the high-affinity synthetic agonist GW3965 was able to repress IFN-gdependent responses in acLDL-induced foam cells, which is in agreement with previous reports demonstrating anti-inflammatory actions of synthetic LXR agonists within the artery wall in vivo (12,50).…”
Section: Discussionsupporting
confidence: 81%
“…Our results with LPS-treated cells support these observations, but the fact that the inflammatory response to IFN-g remains almost unchanged after cholesterol loading is intriguing and may help explain why a considerable percentage of foam cells within established atherosclerotic lesions still display a classically activated phenotype (49). Remarkably, the high-affinity synthetic agonist GW3965 was able to repress IFN-gdependent responses in acLDL-induced foam cells, which is in agreement with previous reports demonstrating anti-inflammatory actions of synthetic LXR agonists within the artery wall in vivo (12,50).…”
Section: Discussionsupporting
confidence: 81%
“…We found that the production of LXRs was upregulated by LPS stimulation (Fig. 1a, b), suggesting that activation of LXRs during stress constitutes an endogenous protective mechanism in human islets, as has been found to be the case in macrophages [13] and human monocytes [12]. Adding GW3965 to LPS-stimulated human islets further upregulated the levels of LXRs (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, in vivo and in vitro studies have demonstrated that activation of LXR agonists antagonises inflammatory gene expression in mouse macrophages [10], microglia and astrocytes [11], and human monocytes [12]. In cultured murine and human macrophages the synthetic LXR agonist GW3965 has been shown to reduce cytokine-induced tissue factor (TF) production [13] and we have previously shown that GW3965 dose-dependently attenuated LPS-induced release of TNF-α and prostaglandin E 2 by hepatic Kupffer cells in vitro as well as in vivo [14]. Human islets exposed to human blood trigger an instant blood-mediated inflammatory reaction, characterised by platelet consumption and activation of the coagulation and complement systems, and this activation may impair engraftment after intraportal islet transplantation [15].…”
mentioning
confidence: 99%
“…LXR ligands repress these genes in macrophages derived from WT, Lxra -/-, and Lxrb -/-mice but are unable to do so in macrophages from Lxrab -/-mice, indicating that both LXR isoforms possess antiinflammatory activity. Subsequent work has suggested that tissue factor and osteopontin, both inflammatory genes associated with an increased risk for developing atherosclerosis, are subject to similar repression by LXR ligands in macrophages (75,76).…”
Section: Lxrs As Regulators Of Macrophage Inflammatory Signalingmentioning
confidence: 99%